ANTI – CRISIS STRATEGIES OF ENTERPRISE PERSONNEL MANAGMENT - Shcherban , O. Ya.; Malik , L. O.; Senyshyn , S. Ye.; Condra , O. R. (The actual problems of regional economy development, 2025)
The article highlights the current problem of enterprise personnel management in the conditions of crisis phenomena, which are increasingly accompanied by the functioning of the modern business environment. The purpose of the article is to investigate the essence, features and effective approaches to the implementation of anti -crisis strategies of personnel management at the enterprise, as well as to identify ways of maintaining labor potential, improving the adaptability of employees and ensuring the stable functioning of the organization in the conditions of crisis phenomena. It is noted that effective personnel policy in the face of uncertainty and turbulence is a key factor in maintaining the competitiveness and stable development of the enterprise. The essence of crisis management of personnel as a purposeful set of actions that ensure the adaptation of the labor collective to changes, cost optimization, reduction of social tension and improving the overall efficiency of the enterprise is revealed. The study systematizes the main anti -crisis strategies used in modern practice: optimization of staff, introduction of flexible forms of employment, improvement of motivational mechanisms, development of professional competencies, active implementation of internal education and retraining programs, strengthening of internal communications. The theoretical value of the study lies in the systematization and generalization of approaches to anti-crisis personnel management in the conditions of modern socio-economic instability. The work examines in detail the concept of "anti-crisis personnel management strategy", identifies its main components and principles of formation. The obtained theoretical provisions can become the basis for further research in the field of crisis management and HR strategies. Particular attention is paid to the role of leadership and strategic HR management in overcoming the consequences of the crisis. The article also provides recommendations for the formation of effective anti -crisis personnel policy, which combines economic feasibility with social responsibility. It is concluded that the transition from the tactics of abbreviations to strategic development of staff, even in the conditions of limited resources. Research materials can be useful for scientists, business managers, HR managers and organizational development professionals.